Structural, interpersonal, psychosocial, and behavioral risk factors for HIV acquisition among female bar workers in Dar es Salaam, Tanzania - Barnhart, Dale A.; Harling, Guy; Muya, Aisa; Ortblad, Katrina; Mashasi, Irene; Dambach, Peter; Ulenga, Nzovu; Mboggo, Eric; Oldenburg, Catherine; Bärnighausen, Till; Spiegelman, Donna (AIDS care, 2019)
In sub-Saharan Africa, female bar workers (FBWs) often serve as informal sex workers. Little is known about the prevalence of HIV and HIV-related risk factors among FBWs in Dar es Salaam (DSM), Tanzania. Using an adapted Structural HIV Determinants Framework, we identified structural, interpersonal, psychosocial, and behavioral risk factors for HIV acquisition. We compared the prevalence of HIV and HIV-related risk factors among a random sample of 66 FBWs from DSM to an age-standardized, representative sample of female DSM-residents from the 2016 Demographic and Health and 2011-2012 AIDS Indicator Surveys. Compared to other women in DSM, FBWs had elevated prevalence of all four groups of risk factors. Key risk factors included gender and economic inequalities (structural); sexual violence and challenges negotiating condom use (interpersonal); depression, post-traumatic stress disorder, and low social support (psychosocial); and history of unprotected sex, multiple sex partners, and high alcohol consumption (behavioral). HIV prevalence did not differ between FBWs (7.1%, 95% CI 3.7-13.3%) and survey respondents (7.7%, 95% CI: 5.3-11.1%), perhaps due to FBWs’ higher - though sub-optimal - engagement with HIV prevention strategies. Elevated exposure to HIV-related risk factors but low HIV prevalence suggests economic, psychosocial, and biomedical interventions may prevent HIV among FBWs in DSM.
Gesehen am 08.06.2020